Enhancing Rescue Operations in Dubai Police’s Transport and Rescue Department through IoT and AI Integration - Salahi , Budoor; Jabbouri, Rachid (Journal of Public Policy and Administration, 2025)
Purpose: This research proposes how all the space, the Internet of Things, and Artificial Intelligence technologies can be better used in the Transport and Rescue Department of the Dubai Police. With the rapid evolution in smart technologies, IoT and AI have much scope to refine rescue operations regarding time management, accuracy, resources, and overall processes. Since the requirements in rescue missions are often complex, including environmental change and the need for urgency, the role of IoT and AI is extremely important in decision-making and successful operation. This study investigates how to employ these technologies within Dubai Police's existing rescue framework, which has gaps such as slow response or response delay and inefficient resource distribution. It aims to explore the potential benefits and challenges that the use of these technologies entails while drawing lessons from global best practices on emergency response more generally. Methodology: Using qualitative and quantitative research methods, including interviews, surveys, observation, global case studies, and reviews of existing literature, the research will make recommendations on how these technologies can be effectively used to enhance the success of rescue missions. By fully embracing the concept of Dubai being a smart city, this research will not only upgrade the local emergency response systems, but it will also create a model for the other regions that want to convert to advanced technologies in rescue operations. At the heart of the research is a goal to reach more efficient, faster, and safer rescue operations that, in turn, ensure public safety in Dubai. Findings: Research results show that the Dubai Police have already started using a variety of technology to ensure smart operations (e.g., SAS analytics and VR training), but IoT and AI integration are hampered by infrastructure, technology training gaps, and interagency coordination issues. Rescuers recognize that AI and IoT can be utilized to help in enhancing situational awareness and speeding the response, however, they also flag issues about cybersecurity and the system's compatibility. Unique Contribution to Theory, Practice and Policy: The implication of the research is two-fold. First, it gives specific, practical recommendations on what to do to enhance Dubai's emergency response system. Second, it presents a scalable model for cities that are trying to equip themselves with smart, technology-driven rescue systems.